Keanekaragaman dan Kelimpahan Serangga Tanah di Hutan Desa Serdang: Keanekaragaman dan Kelimpahan Serangga Tanah di Hutan Desa Serdang Kawasan Tahura Kabupaten Karo Sumatera Utara - Manalu, Perlin B.; Hutasuhut, Melfa Aisyah; Syukriah, (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to assess the diversity index, relative abundance, and evenness of soil insects in the Hutan Desa Serdang, Tahura Area, Karo District, North Sumatra. The methods used include pitfall traps and bait traps with a purposive sampling approach at three observation stations: primary forest, secondary forest, and pine forest. The results show that a total of 1,427 insect individuals were found, comprising 8 orders, 13 families, and 20 species. Odontomachus brunneus exhibited high relative abundance, followed by Entomobrya handschini and Solenopsis invicta, which fall into the category of moderate relative abundance. The diversity index of soil insects is categorized as moderate, with an value of H' = 2.0, indicating a balanced ecosystem with a sufficient variety of species. Meanwhile, the evenness index of soil insects is classified as high, with a value of H'= 0.7. This indicates a uniform distribution of species without particular dominance, thus supporting ecological balance and good soil ecosystem quality.